(untitled) (Linguist, 2026)
This research paper examines the effect of explicit teaching of cognitive strategies related to listening skills in developing active performance of communicative competence among learners of Arabic as a second language.The study starts from a theoretical premise that listening is not a passive reception of linguistic input, but rather a complex interactive cognitive activity that requires the operation of a set of higher mental processes, such as predicting content, constructing meaning based on context, linking auditory data to prior knowledge, self-monitoring of comprehension, and continuous evaluation of performance.The paper adopts a descriptive analytical approach based on a critical review of the most prominent relevant literature in the field of applied linguistics, particularly research related to second language acquisition, cognitive language processing theories, and the communicative approach to language teaching. It also reviews a number of contemporary pedagogical practices that have proven effective in developing listening skills within multilingual and multicultural classroom environments, with an emphasis on the importance of moving from implicit teaching of strategies to explicit and systematic teaching of them.The results of the analysis highlight that explicit teaching of cognitive strategies contributes significantly to raising the level of metacognitive awareness among learners, enhances their ability to control auditory comprehension processes, and positively impacts the quality of their oral communication performance in real-life communication situations. Based on this, the paper proposes a set of pedagogical guidelines and practical projections for developing listening instruction in Arabic language programs for non-native speakers, through the design of authentic communicative tasks, the integration of problem-solving activities, and the use of formative assessment as a tool to support learning.The study concludes that systematic investment in teaching cognitive strategies represents an effective educational approach to enhancing overall communicative competence among learners of Arabic as a second language, and recommends expanding empirical research in this area in diverse educational contexts.